ADHD in adults in a nutshell - Rzeska, Ewa; Jurasz, Karolina; Podgórska, Dominika; Sanecki, Miłosz; Tomczyk, Karolina; Chojnacka, Natalia; Klarycki, Jakub; Cymer, Radosław (Journal of Education, Health and Sport, 2024)
ADHD (attention-deficit hyperactivity disorder), primarily only considered as a childhood condition, remains an underdiagnosed condition that also affects adult patients. High comorbidity and similarities to different psychiatric disorders impedes the diagnosis. Despite this, it is important for medical practitioners to detect ADHD symptoms and implement proper treatment to enhance patients’ life quality. Treatment should be multimodal and involve both behavioral therapy and pharmacotherapy.